Governance and Civil War Onset - Fearon, James D. (World Bank, Washington, DC, 2012)
Supports the view that low-income countries have a greater risk of violent conflict due to poor governance and weak institutions. Some have argued for a direct causal effect via a country's labor market, but a major obstacle to assessing these arguments has been the lack of direct measures of the quality of a country's governance or institutions. Based on various World Bank indexes and indicators, it is possible to assess the impact of the income level on conflict likelihood. Remarkably, given that governance indicators change little over time, even within countries, improvements in governance tend to reduce subsequent conflict risk. Overall, aid in conflict-affected countries needs to do more than try to raise incomes through project lending. If capable government is indeed the root of the problem of conflict and development more than a 'poverty trap,' for example, then a more integrated approach that draws from the peacebuilding and state building experience of UN and other peacekeeping operations may be necessary.